DESCRIPTION OF MOTHERS’ KNOWLEDGE LEVELS ABOUT PNEUMONIA IN TODDLERS IN BEBANDEM DISTRICT, KARANGASEM REGENCY - Permani, Ni Komang Dian; Subanada, Ida Bagus; Trisna Windiani, I Gusti Ayu; Karyana, I Putu Gede (E-Jurnal Medika Udayana; Vol 14 No 2 (2025): E-Jurnal Medika Udayana, 2025)
Pneumonia is a global health problem, which is the main cause of toddler mortality in the world. The high incident of pneumonia in toddlers is influenced by various factors, one of which is the mothers’ level of knowledge. Mother's knowledge about pneumonia is related to the attitude of prevention and child care. Mothers with a good knowledge tend to be more supportive of to prevent pneumonia in their children, and are more aware if they are infected with pneumonia to get treatment more quickly, so as to reduce the number of mortality and morbidity of pneumonia in toddlers. This study aims to describe the level of knowledge of mothers about pneumonia in toddlers. This study is a descriptive study, with a cross-sectional study design. Samples are selected using probability sampling technique with cluster random sampling, on 112 respondents who are mothers of children aged 1 month to 5 years in Bebandem District, Karangasem Regency. The results showed that 50% of mothers had a low level of knowledge about pneumonia in children under five, 30.4% respondents with a low level of knowledge are aged 26-35 years, 19.6% received junior secondar education, and 45.5% have never received information about pneumonia in toddlers. Based on the results of the study, it can be concluded that the level of knowledge of mothers about pneumonia in toddlers in the District of bebandem, Karangasem Regency mostly in low level of knowledge.